Recent Examination of Energy Markets Volatility - Jude Octavian; Turgeman Avraham; Boţoc Claudiu (Studies in Business and Economics, 2023)
The main aim of the paper is to examine if the energy market (crude oil, gas and electricity) realized volatility exhibits a symmetric or an asymmetric behaviour, for certain commodities over the period May 2012 – August 2022. We considered this time frame for data collection because it is ensuing after the extensively researched period of the financial crises that started in 2007. We took into consideration the STOXX Europe 600 index representing large, mid and small capitalization companies across 17 countries from the European Union. Subsidiary we want to examine if there are similarities in term of realized volatility between energy markets and equity markets. For energy markets the results are consistent with the leverage hypothesis of the asymmetric volatility, i.e. negative and positive returns with the same magnitude have different impact on volatility. Furthermore the volatility is more sensitive to its lagged values in the market place than it is to new information. In addition, for the entire period volatility is asymmetric for both energy and equity markets, but there are different sub-periods with different results. These results reinforce the diversification principle that must be considered in portfolio and risk management process.